2020
DOI: 10.1093/cs/cdaa021
|View full text |Cite
|
Sign up to set email alerts
|

School Crisis Management Planning

Abstract: The fundamental need for safety in schools requires research-based and trauma-informed strategies for implementing crisis management plans (CMPs). Beyond the immediate harm, longer-term potential outcomes of crises are psychological trauma and damage to the reputation for safety of the school, leading to staff attrition. An effective CMP involves (a) planning, (b) communication, (c) protocols for immediate action, and (d) protocols specific to different types of school crises. School crises can occur on the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Research conducted in various regions of Turkey also shows that one of the lowest-rated items perceived during the pre-crisis period is "creating crisis scenarios before a crisis occurs" (Bıyıklıoğlu, 2020;Maya, 2014;Sağlam & Özsezer, 2015;Ulusoy, 2020). Therefore, it can be said that school principals in various regions of Turkey may lack the necessary experience (McCarty, 2012;Trethowen, 2009) and creative thinking skills (Elbedour, 2020;Smith & Riley, 2012) to imagine possible scenarios for potential crises.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research conducted in various regions of Turkey also shows that one of the lowest-rated items perceived during the pre-crisis period is "creating crisis scenarios before a crisis occurs" (Bıyıklıoğlu, 2020;Maya, 2014;Sağlam & Özsezer, 2015;Ulusoy, 2020). Therefore, it can be said that school principals in various regions of Turkey may lack the necessary experience (McCarty, 2012;Trethowen, 2009) and creative thinking skills (Elbedour, 2020;Smith & Riley, 2012) to imagine possible scenarios for potential crises.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them avoided collaboration and adhered only to MoNE guidelines. When reviewing the literature, it is observed that during crisis interventions, school administration and the guidance service are actively involved (Çelebi, 2019), and school principals seek the most support from guidance counsellors in crisis resolution (Tokel, 2018), as effective crisis management is rooted in planning, with psychologists playing a key role (Elbedour, 2020). In this context, it can be said that during the post-crisis period, the steps taken by school principals to support the psychological well-being of students are functionally dependent on the crucial role of guidance counsellors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr Fleming could have improved trust and cooperation with stakeholder groups through two-way communication, which creates a community of practice, in which stakeholders collaborate. During a crisis, such as a pandemic, clear and continual communication is vital to maintain trust and safety in a school or district (Coombs, 2014;Elbedour et al, 2020). Even when meeting an unprecedented challenge with potentially changing policies, district leaders can maintain teacher morale through transparency and clear communication with teachers' unions (Hemphill & Marianno, 2021).…”
Section: Teaching Notesmentioning
confidence: 99%
“…Most studies tend to follow a biomedical approach and concentrate on the sequence “crisis – trauma – diagnosis – clinical intervention for at-risk individuals” (e.g. Elbedour et al, 2020; Nickerson & Zhe, 2004). While these interventions have their place in helping those who have been most deeply impacted by the crisis, they risk missing the opportunity to reach all individuals who would benefit from preventive and empowering activities.…”
mentioning
confidence: 99%